Physical Activity: A Means of Enhancing Health and Well-Being of the Elderly in the Nigerian Populace - Surajudeen Tosho Bakinde; O. L. Olaitan; O. L. Dominic (Indonesian Journal of Educational Research and Review)
Physical inactivity and sedentariness are becoming rampant among the elderly within the Nigerian population. The reasons are traceable to changes in lifestyle as a result of diet, social activity and orientation. Most of the elderly believe that they need more rest out their age and should not subject their body to stress. However, experience has revealed that a lot of them experience health challenges that could have been averted if they were physically active. This study identified the causes of inactivity, addressed the importance and benefits of physical activity on health and well-being of the elderly in the Nigerian populace. The study also advocated for a need to engage and physical activity and the type of activities that are beneficial to the health of the elderly people. This study concluded by suggesting ways of overcoming identified barriers to physical activity participation. It was recommended that stakeholders such as medical, paramedical, sports and exercise scientists and other practitioners should develop programmes to address the problem of physical inactivity and facilitate behavioural change among the elderly.